Novel GUCY2D Splicing Variants in Kurdish Leber Congenital Amaurosis Patients in Iraq - Rwandzy, Hozan I.; Hidayat, Hazha J. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
The current study examines the single-nucleotide polymorphism of the GUCY2D gene in blind patients with inherited Leber congenital amaurosis (LCA) from a molecular, medical, and genetic perspective. The study involved 33 patients with blindness and 11 healthy controls in Erbil Province, Kurdistan Region, Iraq. LCA is the most severe phenotype of inherited retinal diseases, marked by genetic and clinical heterogeneity. The goal of this work was to confirm and identify the underlying mutations. The visual evoked potentials (VEPs) test, fundus photography, and ophthalmic examination were the foundation for clinical studies. Each participant’s genomic DNA was extracted to ascertain the frequency of mutations in the Kurdish nation. Primers were designed for the GUCY2D gene, encompassing exons 15, 16, and part of 17, with introns situated between those exons. Potentially pathogenic mutations were detected using Sanger sequencing analysis of the GUCY2D gene. Sequence data were analyzed to identify known, unknown, or novel mutations using FinchTV, BioEdit, and databases from the National Center for Biotechnology Information, including BLASTN, BLASTX, and ClinVar, along with Mutation Surveyor and MaxEntScan. Three novel splicing mutations have been found in the GUCY2D of blindness patients. These mutations are: c.3043+11C>T, c.3044-7G>T, and c.3043+20G>C. The patients have included nystagmus, abnormal VEPs, photophobia, hyperopia, and early infantile onset of vision loss. The three new mutations in the GUCY2D of Kurdish blind patients are associated with LCA disease. A family history of blindness or the presence of affected relatives may represent important risk factors for LCA, supporting its inherited genetic basis.